Optimization of Transportation Costs With The Implementation of The Milk-Run Method - Kurbandi Satpatmantya Budi Rochayata; R.R. Wening Ken Widodasih; Hery Gunardi (Institute of Computer Science (IOCS), 2022)
The rapid development of technology and information affects the development of international logistics. These developments have an impact on efficiency and effectiveness in logistics processes which include integration of information, transportation, inventory, warehousing and distribution so that in the global logistics business, service providers compete to reduce logistics costs and maximize logistics services. The purpose of this research is to obtain the most appropriate and optimal pick-up and delivery transportation system that can minimize transportation costs. The population in this study is data from PT. Nippon Express Indonesia, and the sample of this study is data from November 2021. Analysis of determining distribution routes using the Milk-Run method. By using the Milk-Run method, the number of truck fleets can be reduced from 4 trucks to only 1 truck. The original mileage of 133.1 kilometers can be reduced to 74.8 kilometers, which means distance the could shortened/more economical as big as 44.1 % or around 58.3 kilometers. The reduction in trucks resulted in lower transportation costs. The original cost was Rp. 8,670,000 down to Rp. 6,300,000. Thus, there is a savings in distribution channel costs of Rp.2,370,000 or approximately 27.03%.